Identification of a population of peripheral sensory neurons that regulates blood pressure - Morelli, Chiara; Castaldi, Laura; Brown, Sam J.; Streich, Lina L.; Websdale, Alexander; Taberner, Francisco J.; Cerreti, Blanka; Barenghi, Alessandro; Blum, Kevin M.; Sawitzke, Julie; Frank, Tessa; Steffens, Laura K.; et al. (Cell reports, 2021)
The vasculature is innervated by a network of peripheral afferents that sense and regulate blood flow. Here, we describe a system of non-peptidergic sensory neurons with cell bodies in the spinal ganglia that regulate vascular tone in the distal arteries. We identify a population of mechanosensitive neurons, marked by tropomyosin receptor kinase C (TrkC) and tyrosine hydroxylase in the dorsal root ganglia, which projects to blood vessels. Local stimulation of TrkC neurons decreases vessel diameter and blood flow, whereas systemic activation increases systolic blood pressure and heart rate variability via the sympathetic nervous system. Ablation of the neurons provokes variability in local blood flow, leading to a reduction in systolic blood pressure, increased heart rate variability, and ultimately lethality within 48 h. Thus, a population of TrkC+ sensory neurons forms part of a sensory-feedback mechanism that maintains cardiovascular homeostasis through the autonomic nervous system.